Analysis of Innovation in Public Service (Research Study on Banjarbaru City, Batam City, and Bandung City) - Heri Wahyudianto (Inovbook Publications, 2021)
This study aims to analyze the innovations that have been made by various cities that have the aim of improving the quality of public services. This research uses a qualitative approach. The technique of collecting data by researchers is by conducting literature studies related to research in order to obtain concepts that are relevant to the study of public policy innovation. The population in this study are cities that have made innovations in public services, while the samples in this study are innovations made by the city of Bandung, Banjarbaru city, and also the city of Batam which has the aim of improving the quality of public services in each city. The results obtained in this study are the existence of innovations made by various regions, indicating that what is done will be encourage the development of public service innovation, encourage the development and transfer of public service innovation, accelerate the improvement of the quality of public services, and also improve community satisfaction. Where innovation is carried out in the form of combining new elements, new combinations of existing elements, significant changes or starting from traditional ways of doing things, as well as referring to new products, new policies and programs, new approaches, and new processes.